Trends and regional variations in chronic ischemic heart disease and lung cancer-related mortality among American adults: Insights from retrospective CDC wonder analysis - Eman Ali; Hafsah Alim Ur Rahman; Usama Hussain Kamal; Muhammad Ahmed Ali Fahim; Madiha Salman; Afia Salman; Hamza Nawaz Khan; Farah Yasmin; Chmsalddin Alkhas; Afsana Ansari Shaik; Muhammad Sohaib Asghar; M. Chadi Alraies (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Introduction: Lung cancer remains the leading cause of cancer-related mortality in the United States and shares cardiovascular risk factors with chronic ischemic heart disease (CIHD). However, the cumulative mortality burden of these comorbid conditions is underexplored. This study aims to retrospectively assess mortality trends among American adults with concurrent lung cancer and CIHD. Methods: We utilized death certificate data from the Centers for Disease Control and Prevention's Wide-Ranging Online Data for Epidemiologic Research (CDC WONDER) database, encompassing ICD-10 codes for individuals aged ≥45 years from 1999 to 2020. Age-adjusted mortality rates (AAMRs) per 100,000 population, annual percentage change (APC), and corresponding 95 % confidence intervals (CIs) were calculated. Data were further stratified by year, sex, race, and geographic region (state, rural-urban, and census regions). Results: A total of 214,785 deaths were identified in adults aged ≥45 years with comorbid lung cancer and CIHD. The overall AAMR between 1999 and 2020 was 8.4 per 100,000 (95 % CI: 8.3 to 8.4). AAMRs remained relatively stable from 1999 to 2005 (APC: −0.84 %; 95 % CI: −1.91 to 1.54), followed by a significant decline from 2005 to 2010 (APC: −2.37 %; 95 % CI: −5.58 to −0.61) and from 2010 to 2017 (APC: −4.72 %; 95 % CI: −7.61 to −3.60). A subsequent period of stability was noted between 2017 and 2020 (APC: 0.86 %; 95 % CI: −2.17 to 5.22). In 1999, men had a threefold higher mortality rate compared to women (AAMR: 17.8 vs. 5.7), with a non-significant decline by 2020 (AAMR: 10 vs. 4). Stratification by race/ethnicity revealed that non-Hispanic (NH) Whites exhibited the highest AAMR at 9.3, followed by NH American Indian or Alaska Natives (7.3), NH Blacks (6.8), Hispanic/Latinos (3.3), and NH Asians or Pacific Islanders (3.2). Geographically, AAMRs were highest in the Midwest (9.6), followed by the Northeast (8.8), South (8.4), and West (6.8). Non-metropolitan regions exhibited higher AAMRs compared to metropolitan areas (10.3 vs. 8.0). States in the top 90th percentile, such as West Virginia, Kentucky, Vermont, Ohio, and Rhode Island, had nearly triple the AAMRs compared to states in the lower 10th percentile, including Utah, Nevada, Arizona, New Mexico, and Hawaii. Conclusions: From 1999 to 2020, mortality rates for adults aged ≥45 years with concurrent lung cancer and CIHD declined. The highest AAMRs were observed among men, NH Whites, individuals residing in the Midwest, and non-metropolitan populations. This highlights the need for a more comprehensive and tailored approach to managing these patients moving forward.